Employment Impacts of Climate Change Mitigation Policies in OECD A General-Equilibrium Perspective - Château, Jean (OECD Environment Working Papers, 2011)
Using a computable general equilibrium, this paper quantifies the GDP and employment effects of an illustrative greenhouse gas emissions reduction policy. The paper first analyses the direct negative economic effects of the emissions restrictions on GDP and examines labour sectoral reallocations in a framework where labour markets are perfectly flexible. The model is then modified to incorporate labour market imperfections in OECD countries that could generate unemployment, namely, short-run rigidities in real wage adjustment. It is shown that imperfect wage adjustment increases the cost of mitigation policy since unemployment increases in the short-run, but that the carbon tax revenue generated can be recycled so as offset some or all of this effect, notably when it is used to reduce wage-taxes. Thus, taking realistic labour market imperfections into account in a CGE model affects the GDP costs of mitigation policy in two ways: first by introducing extra costs due to the increased unemployment that such policy may entail; second by creating the possibility of a double dividend effect when carbon taxes are recycled so as to reduce distorting taxes on labour income..